Wartime protected area governance: the case of Colombia's Alto Fragua Indiwasi National Park. Issue 6 (14th May 2021) - Gorricho, Julia; Schultze-Kraft, Markus
Abstract: Despite its relevance for conservation in biodiversity hotspots, many of which are in the Global South and display a record of violent conflict, the relationship between protected area governance and armed conflict is underexplored. While a rich literature on protected area governance documents the existence of different governance types, ranging from state-led to community-organised conservation initiatives, thus far scholars have not examined in any depth what kinds of protected area governance arrangements and institutions emerge and operate under conditions of violent conflict. Working with a neo-institutionalist framework, the present article provides evidence regarding the impact of armed conflict on one protected area governance system in Colombia: Alto Fragua Indiwasi National Park in the southern department of Caquetá. The analysis is based on a review of the existing literature on protected area governance and armed conflict and in-depth fieldwork with key park and other stakeholders, carried out in Colombia in 2016. The research finds that despite the formidable challenges faced by the National Park Team amid armed conflict, certain conservation outcomes could still be achieved as a result of the adaptation of the park governance system.